New Psychoactive Substances and receding COVID-19 pandemic: really going back to “normal”? - Napoletano, Simona; Basile, Giuseppe; Lo Faro, Alfredo Fabrizio; Negro, Francesca (Acta Biomedica Atenei Parmensis, 2022)
To the Editor, The ongoing rise of New Psychoactive Substances (NPS), i.e. psychotropic molecules devised and synthesized to replicate the effects of traditional drugs of abuse in order to circumvent banned substances schedules, has been posing a challenge of enormous magnitude to substance detection systems and law enforcement worldwide. Still, it would be remiss to ignore the role played by the unprecedented public health emergency relating to the COVID-19 pandemic in the exacerbation of the NPS crisis. The diversion of resources has in fact hindered conventional approaches to drug monitoring, surveillance, control, and public health responses. The dangerous path ahead in our struggle against NPS abuse is best exemplified by the rather recent emergence of isotonitazene, an analogue of a benzimidazole class of analgesic compounds, powerful synthetic opioid and full mu-opioid receptor agonist belonging to the 2-benzylbenzimidazole group of compounds, which comprises the structurally different clonitazene, metonitazene and etonitazene (1). Isonitazene has reportedly been detected on European markets in at least five different forms and could even supplant fentanyl derivatives (2). Currently available data on isonitazene-related abuse and fatalities seem to be emblematic of the volatile, elusive nature of NPS: deaths in which isotonitazene was involved in fact presented substantial differences from casualties arising from synthetic opioids abuse. Case reports have highlighted how flualprazolam was detected in most fatalities associated with isotonitazene whereas flualprazolam was involved in only 8% of other synthetic opioid overdose deaths (3). Rather than rising background use, such a finding seems to suggest likely co-use or co-distribution of flualprazolam and isotonitazene. The key element of polysubstance involvement is rife in synthetic opioid overdose deaths. That being said, significantly more substances were implicated in isotonitazene-related deaths than fatalities linked to other synthetic opioid overdose (4, 5). Such dynamics and mortality patterns further stress the urgency of expanding health services for those suffering from opioid addiction disorders. Fine-tuned and standardized detection mechanisms relying on specialized assays based on sensitive instrumentation are essential for the timely and accurate characterization of such novel synthetic opioids (6-8). Isotonitazene in fact cannot be detected by common fentanyl testing strips (9). Hence, the essential nature of clinical and toxicological cannot be overstated, if we are to effectively deal with the public health risks arising from new substances or classes, along with the healthcare and social costs thereof (10). As new substances appear on illicit markets and are detected, their distinctive traits can only be identified by user experience, in the early stages (11-13). Nonetheless, the pandemic scenario has brought about a profound alteration of substance abuse patterns, and opened up new avenues of supply and demand for which our surveillance/detection systems may not be fully prepared or well-suited. As the pandemic appears to recede and hopefully turn into an endemic context based on coexistence with the SARS-CoV-2 and its less harmful variants, it would be a mistake to take for granted that drug abuse/trafficking dynamics will also get back to where they were before the pandemic. Putting in place policies aimed at monitoring web-based platforms and social media can potentially constitute a valuable tool in terms of keeping in check emerging substances, given how during the COVID-19 pandemic many interactions between traffickers and buyers have moved online (14). After all, social media have been playing an increasingly relevant role as interacting platforms, which users and drug dealers can take advantage of in order to discuss drug prices, substance purity, distinctive traits of the “high” (i.e. desired drug effects) they are seeking, ways of taking the substances, dosages, and characteristics of any new NPS becoming available on such back-alley marketing channels (15). Softwares designed and specifically programmed to sift through and analyze all detectable online information in that regard may prove valuable to figure out evolving dynamics of trafficking, purchases and use. Probing social media users has proven effective tool for public health concerns, e.g. drug checking services which have been harnessed due to their harm reduction potential in places estimated to be at risk, with large crowds gathering (concerts, clubs and the like). Nonetheless, research efforts need to be directed towards the new realm of criminality, the “Dark Web”, in which all sorts of illegal exchanges and interactions are known to take place. A 2020 study has highlighted the appalling risks for drug users who choose to pursue that option in order to buy drugs (16). Three dealers were selected on a specific “Dark Web” marketplace, and NPS were ordered through such a channel. All these exchanges were thoroughly documented, and an analysis was undertaken of all the substances thus bought, totaling nine samples, by NMR, HRMS, LC-UV, and two also by x-ray diffraction. It was ultimately concluded that four out of five substances bought had been labeled with NPS names that did not match the actual substance, and two out of three samples of substances sold as new (i.e. unscheduled) NPS were instead found to be already documented substances, mislabeled and peddled under false pretenses. Drug dealers were therefore either deceiving their clients or were unaware as to the actual substances which they were selling. In light of such extremely worrisome findings, it is not hard to understand the implications and the major public health risks that such new trends of trafficking and abuse may entail. It is therefore incumbent upon the scientific community and law enforcement agencies to adapt and strive to meet the new challenges brought by the new criminal ecosystems in terms of drug enforcement, first and foremost the impervious environment known as “Dark Web” relying on untraceable cryptocurrencies for illegal transactions.